Pre-Service English Teachers’ Challenges of Teaching Practicum in Teaching Assistance (AjarMi) Program - Fadillah, Fadillah; Jabu, Baso; Muhallim, Muhallim (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
This study aims to find out pre-service English teachers’ challenges of teaching practicum and how they overcome them. Interviews as the instruments used in this study and employed multiple case studies. Pre-service English teachers who participated in AJARMI program in the academic year 2022–2023 served as the study's subjects. Three PSETs participated in interviews. The findings of this study were analyzed using thematic analysis. The PSETs faced challenges related to students' behaviour, preparation of instructional materials, and mentoring. Then they handled them with organizing lessons, acting as an assertive teacher, devising a backup plan, and adapting to the school system.Keywords: Pre-service English Teachers, Teaching Practicum